Parent Beliefs About the Causes of Learning and Developmental Problems Among Children With Autism Spectrum Disorder: Results From a National Survey. - Zuckerman, Katharine E.; Lindly, Olivia J.; Sinche, Brianna (American Journal on Intellectual & Developmental Disabilities, 2016)
This study aimed to assess variation in parent beliefs about causes of learning and developmental problems in U.S. children with autism spectrum disorder, using data from a nationally representative survey. Results showed that beliefs about a genetic/hereditary cause of learning/developmental problems were most common, but nearly as many parents believed in exposure causes. Forty present of parents had no definite causal beliefs. On multivariate analysis, parents who were non-White, publicly insured or poor were more likely than other parents to endorse exposure causes, or less likely to endorse genetic causes, compared to other parents. Further research should assess how these beliefs modify health care quality or services use.